2021
DOI: 10.1039/d0ra10445k
|View full text |Cite
|
Sign up to set email alerts
|

Selective extraction of trivalent actinides using CyMe4BTPhen in the ionic liquid Aliquat-336 nitrate

Abstract: Improving the kinetics of selective An(iii) extraction from nitric acid feed solutions into an ionic liquid based solvent: combining CyMe4BTPhen with TODGA in Aliquat-336 nitrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The electrode potential of the P9 complex ( E 1/2 = −0.56 V vs SHE) is much more negative than that of the hydrated Eu complex ( E 1/2 = −0.35 V vs SHE), which clearly indicates that the L 4 ligand destabilizes the divalent state of Eu . Therefore, [Eu II (T1) 3 (NO 3 ) 2 (H 2 O)] is lesser resistance to oxidation as compared to Eu 2+ (aq) , , which implies that the [Eu III (T1) 3 (NO 3 ) 2 (H 2 O)] + complex is more stable than its analogous [Eu II (T1) 3 (NO 3 ) 2 (H 2 O)].…”
Section: Resultsmentioning
confidence: 99%
“…The electrode potential of the P9 complex ( E 1/2 = −0.56 V vs SHE) is much more negative than that of the hydrated Eu complex ( E 1/2 = −0.35 V vs SHE), which clearly indicates that the L 4 ligand destabilizes the divalent state of Eu . Therefore, [Eu II (T1) 3 (NO 3 ) 2 (H 2 O)] is lesser resistance to oxidation as compared to Eu 2+ (aq) , , which implies that the [Eu III (T1) 3 (NO 3 ) 2 (H 2 O)] + complex is more stable than its analogous [Eu II (T1) 3 (NO 3 ) 2 (H 2 O)].…”
Section: Resultsmentioning
confidence: 99%
“…Systems with bis-triazinyl ligands are characterized by low extraction rates, [12][13][14][15][16] which in some cases require the application of interfacial catalysts to accelerate the extraction process. 17,18 For ligands that take a long time to reach equilibrium, utilizing a test-tube experiment to study the kinetics offers a convenient and straightforward approach. It facilitates the comparison of several ligands with each other and the establishment of structure-property patterns.…”
Section: Introductionmentioning
confidence: 99%
“…15 diluent for separating actinides from lanthanide series, effectively resolving the sluggish kinetics even at elevated temperatures. 16 For many soft N-donor and S-donor ligands, the extended actinide 5f orbitals can be distinguished from the more contracted lanthanide 4f orbitals. The covalent interaction between the soft N-or S-donor ligands and the 5f orbitals of An(III) is significantly stronger than that with the 4f orbitals of Ln(III).…”
Section: Introductionmentioning
confidence: 99%
“…Bis-triazinyl-pyridine (BTP), composed solely of carbon (C), hydrogen (H), oxygen (O), and nitrogen (N), is a promising candidate extractant that exhibits excellent performance and generates no secondary waste. , 6,6′-Bis­(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzol­[1,2,4]­triazin-3-yl)­[2,2]­bipyridine (CyMe4-BTBP) is another effective extractant known for its resistance to acidic environments and the intense radiation of radiolysis present during the separation. , Additionally, 2,9-bis­(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-1,2,4-benzotriazin-3-yl)-1,10-phenanthroline (CyMe4-BTPhen) possesses higher surface activity at the organic/water interface than CyMe4-BTBP due to higher local concentrations . Zsabka et al demonstrated that [A336]­[NO3]/CyMe4-BTPhen could be utilized either with or without a phase transfer catalyst and co-diluent for separating actinides from lanthanide series, effectively resolving the sluggish kinetics even at elevated temperatures …”
Section: Introductionmentioning
confidence: 99%